Clinical Significance of Ultrasonographic Findings in Dengue Patients; The Comparison of 2019 and 2022 Out Breaks - Baseer, Maliha; Shan, Saima; Rehman, Asim; Ilyas Dar, Savida (Pakistan Armed Forces Medical Journal, 2023)
Objective: To signify the ultrasonographic findings as an adjunct to serological diagnosis of dengue fever and to correlate ultrasound findings of dengue patients from the disease outbreak in 2019 and 2022 Pakistan with serological parameters such as platelet count, WBC and hematocrit.Study Design: Prospective longitudinal study.Place and Duration of Study: Radiology Department, Federal Government Polyclinic (PGMI), Islamabad, Pakistan from Jan2019 to Dec 2022.Methodology: All patients referred to the Radiology Department for an Ultrasound Abdomen, who were admitted to the Hospital Isolation Unit and were found to have anti-dengue serology, were included in the data. Ultrasonographic findings of dengue patients from the disease outbreak in 2019 and 2022 along with serological parameters such as platelet count, WBC and Hematocrit were assessed.Results: Out of 343 diagnosed dengue fever patients from the 2019 and 2022 outbreaks Pakistan, the majority (n=176; 51.3%) patients had thickening of the gall bladder wall finding, followed by hepatomegaly (n=100; 29.2%), ascites (n=94;27.4%), pleural effusion (n=84; 24.5%), splenomegaly (n=47; 13.7%) and perinephric fluid (n=8;2.3%). Thickness of the gallbladder (n=90; 68.2%) wall was most common in cases with platelet counts